Spazas, hawkers and the status quo: Black consumption at the margins of media discourse in post-apartheid South Africa - Iqani, Mehita (Animus. Revista Interamericana de Comunicação Midiática, 2012)
http://dx.doi.org/10.5902/217549777298 This paper examines the mediated marginalization of forms of black consumption that were considered unthreatening to South Africa’s economic elite during the 1990s, South Africa’s first decade of political freedom. It argues the English language press of the time treated certain practices of black consumption produced, and approved of, by Apartheid state structures as natural, and as such contributed to a propping up of the economic status quo in the face of a sea change in the political environment. The paper offers as a theoretical framework a discussion of the tensions between citizenship and consumption in South Africa, and the complexity of claims that consumption equals empowerment in post-colonial contexts. Next, a brief account is provided of the process of constructing the corpus of media texts analyzed. Finally, the paper presents the key themes of the ways in which black consumption was discursively marginalized and critically discusses those in relation to bigger questions about the extent to which consumption stands for empowerment in post-Apartheid South Africa.